2016
DOI: 10.1080/14766825.2016.1246555
|View full text |Cite
|
Sign up to set email alerts
|

Touring the ‘comuna’: memory and transformation in Medellin, Colombia

Abstract: The objective is to explore the touristification of some peripheral neighbourhoods of Medellin. The focus is on urban areas built by wardisplaced populations commonly referred to as 'comunas' and often associated with crime and narco-traffic. Some tours generally labelled as 'comuna tours' have been emerging the last three years and are largely included in the promotion of the 'new Medellin', focusing on its transformation from 'the most violent to the most innovative city in the world'. Examining the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 12 publications
0
30
0
3
Order By: Relevance
“…In other words, while this tour may now feature as a 'top cultural choice' in the Lonely Planet travel bible, its local recognition is still limited. Similarly, the author personal research in Medellin (Naef 2016a(Naef , 2018a has shown that tours focusing on the violent past of the second city of…”
Section: Tourism Stakeholders and Narcos As Memorial Entrepreneurs Inmentioning
confidence: 95%
“…In other words, while this tour may now feature as a 'top cultural choice' in the Lonely Planet travel bible, its local recognition is still limited. Similarly, the author personal research in Medellin (Naef 2016a(Naef , 2018a has shown that tours focusing on the violent past of the second city of…”
Section: Tourism Stakeholders and Narcos As Memorial Entrepreneurs Inmentioning
confidence: 95%
“…'Comuna tours' (Naef, 2016) referring to the common designation of these urban areas as 'comunas', explore specific parts of these neighbourhoods, looking at their violent past, but also at contemporary issues of violence, setting them against the creativity and resilience of their inhabitants. These tours generally offer a narrative closely associated with the urban transformation and social investments that can be seen in the city.…”
Section: Escobar Narco-aesthetic and Tourismmentioning
confidence: 99%
“…Mémoire, transformation et « disparitions forcées » à Medellin 21 Medellin est réputée comme la ville ayant passé du statut de la « plus violente à la plus innovante du monde », depuis les politiques d'urbanisme social développées dès 2004 par le maire de l'époque, Sergio Fajardo. Ce discours promotionnel, basé sur une image héroïsante des transformations urbaines qui caractérisent Medellin, tend à obscurcir la mémoire du conflit armé que de nombreux acteurs -politiques, urbanistes, promoteurs touristiques -aimeraient oublier (Naef, 2016(Naef, , 2016a. Dans ce contexte, les revendications d'entrepreneurs mémoriels investis dans la mise en mémoire d'événements controversés comme l'opération Orion peuvent se heurter à une forme d'immobilisme des pouvoirs publics.…”
Section: L'escombrera : D'une Décharge Municipale à Une Fosse Communeunclassified
“…5 Cette contribution se base sur une recherche ethnographique plus vaste menée en 2015 à Medellin sur les pratiques d'entrepreneurs mémoriels dans les quartiers périphériques de la ville -communément qualifiés des « comu nas », du nom des divisions administratives qui composent la ville, au nombre de 16 pour Medellin -pour explorer certaines stratégies mises place afin d'exposer une mémoire violente et dissonante (Tunbridge & Ashworth, 1996). Ceci dans un contexte où certains éléments mémoriaux sont obscurcis par des discours hégémoniques sur la transformation de la ville de la plus « violente à la plus innovante du monde » (Naef, 2016(Naef, , 2016a. Durant plusieurs mois, j'ai observé et participé à certains événements et activités visant à mettre en lumière la mémoire du conflit urbain qui a fortement traumatisé ces quartiers.…”
unclassified